2005
DOI: 10.1051/agro:2004065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fertilizer rate and water irrigation quality on the recovery of 15N-labeled fertilizer applied to Sudangrass

Abstract: Wastewaters are increasingly used for irrigation of cropping systems in Tunisia. However, to develop environmentally sound practices the contribution of wastewater to crop N nutrition needs to be clarified, especially in cropping systems already receiving mineral fertilizers. For a better understanding of the interaction between fertilizer N and N originating from wastewater, experiments using 15 N were conducted. 15 N-labeled fertilizer was applied at different rates (0, 60, 100 and 140 kg N•ha-1) and with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
2
4
0
1
Order By: Relevance
“…The NUE decreased from 74.49% to 68.38% by increasing the rate from 120 to 180 kg N/ha. These results are similar to those reported by [32,33]. The 120 kg N/ha rate provides the best efficiencies.…”
Section: Nitrogen Use Efficiencysupporting
confidence: 90%
“…The NUE decreased from 74.49% to 68.38% by increasing the rate from 120 to 180 kg N/ha. These results are similar to those reported by [32,33]. The 120 kg N/ha rate provides the best efficiencies.…”
Section: Nitrogen Use Efficiencysupporting
confidence: 90%
“…Within the agronomic literature, the amount of 15 Nlabelled fertilizer recovered by the target crop typically incrases with increasing rates of fertilizer N addition, with or without irrigation (Pilbeam et al 1997;Tran and Tremblay 2000;Khelil et al 2005). The absence of a fertilizer rate effect (or any interaction thereof) on the Fig.…”
Section: Rootsmentioning
confidence: 99%
“…The trace of nitrogen constituents in agricultural soil has been previously estimated from nitrogen isotope experiments, especially labeled 15 N compounds, particularly for estimating the efficiency of fertilizer use [ Azam et al ., ; Isfan , ; Khelil et al ., ; Rahman et al ., ; Kchaou et al ., ] and the ultimate fate of the applied fertilizer [ Bedard‐Haughn et al ., ; Jenkinson et al ., ; Stevens et al ., , ; Sebiloa et al ., ]. It was observed that the availability of nitrogen to plants from the fertilizer dependents on an interplay between the fertilizer type (such as ammonium, nitrate, and urea), crop and soil characteristics, field management, and weather.…”
Section: Introductionmentioning
confidence: 99%